1990
DOI: 10.1161/01.res.67.2.319
|View full text |Cite
|
Sign up to set email alerts
|

Profound spatial heterogeneity of coronary reserve. Discordance between patterns of resting and maximal myocardial blood flow.

Abstract: We examined the ability of individual regions of the canine left ventricle to increase blood flow relative to baseline rates of perfusion. Regional coronary flow was measured by injecting radioactive microspheres over 90 seconds in seven anesthetized mongrel dogs. Preliminary experiments demonstrated a correlation between the regional distributions of blood flow during asphyxia and pharmacological vasodilatation with adenosine (mean r = 0.75; 192 regions in each of two dogs), both of which resulted in increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
57
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(67 citation statements)
references
References 37 publications
8
57
2
Order By: Relevance
“…This may apply even more for SPECT measurements because of technical issues and count statistics including lower spatial resolution, which may affect the apparent perfusion values in a nonhomogeneous manner, leading to different patterns in the polar plots for PET and SPECT as depicted in Figures 3 and 4. Differences are also based on biologic variability, because a profound spatial heterogeneity has been observed in regional MBF at rest and in response to vasodilator stress (34,35). The anatomic variability of the coronary trees is another source that has been shown to affect the persegment performance of quantitative MBF measurements.…”
Section: Discussionmentioning
confidence: 99%
“…This may apply even more for SPECT measurements because of technical issues and count statistics including lower spatial resolution, which may affect the apparent perfusion values in a nonhomogeneous manner, leading to different patterns in the polar plots for PET and SPECT as depicted in Figures 3 and 4. Differences are also based on biologic variability, because a profound spatial heterogeneity has been observed in regional MBF at rest and in response to vasodilator stress (34,35). The anatomic variability of the coronary trees is another source that has been shown to affect the persegment performance of quantitative MBF measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In 1990, a study in dogs found that coronary flow reserve is spatially heterogeneous and determined by two distinct perfusion patterns: the resting (control) pattern and the maximal perfusion pattern (1). Normal hearts, therefore, contain small regions that may be relatively more vulnerable to ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Normal hearts, therefore, contain small regions that may be relatively more vulnerable to ischemia. This may explain the patchy nature of infarction with hypoxia and at reduced perfusion pressures as well as the difficulty of using global parameters to predict regional ischemia (1).…”
Section: Discussionmentioning
confidence: 99%
“…Sestier et al (48) found an increase in dispersion of relative regional myocardial flows in dogs, from 22 to 31%, with an adenosine-induced fourfold flow increase while coronary pressure was held constant. Austin et al (2,3) showed with intracoronary adenosine infusion in dogs, elevating flow by 5 to 10 times, that the RD of LV regional flows increased from 20% during the control state to 30%, using piece size resolution of 1% of LV mass. At the same time, the "tracking" or the maintenance of rank position in relative regional flow was almost abolished by hypoxia and by adenosine administration.…”
mentioning
confidence: 99%